PENGARUH TINGKAT PENDIDIKAN DAN PENEMPATAN KERJA TERHADAP KINERJA PEGAWAI PADA DP3AP2KB KABUPATEN BIMA - Junita, Dewi; Mukmin, Amirul (Jurnal Manajemen, 2022)
This study aims to determine the effect of the level of relationship and work placement on employee performance at DP3AP2KB Bima Regency. This type of research is associative using quantitative data types from primary data sources. The research instrument used in this study was a Likert scale questionnaire. The population used in this study were all employees at DP3AP2KB Bima Regency, totaling 101 people, which were divided into 72 ASN, 20 honorary employees and 9 volunteer employees. . The sample in this study were 72 civil servants. The sampling technique used in this research is purposive sampling technique. The sample criteria in this study were employees who had ASN status, totaling 72 respondents. Data collection techniques are observation, interviews, documentation, questionnaires and library studies, data analysis techniques using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, multiple correlation coefficients, determination tests, t tests and f tests, The results of the study show that there is a joint influence between the level of education and work placement on employee performance at DP3AP2KB Bima Regency.